Smart lighting control with workspace and ceiling sensors. (June 2017) - Caicedo, D; Li, S; Pandharipande, A
We consider energy-efficient indoor lighting control for adapting to daylight and user presence changes. Light sensors located at ceiling luminaires and at workspace desks are used to provide illumination information feedback, along with user presence information from occupancy sensors at ceiling luminaires, to a lighting controller. The light sensors at the workspace transmit information at a lower update rate than the sensors at the ceiling. Using this sensing information, we propose a control method to adapt the dimming levels of the luminaires such that desired illumination levels are achieved at the workspace level. The performance of the proposed method is evaluated in an office lighting testbed.